1894
DOI: 10.1051/jphystap:018940030039300
|View full text |Cite
|
Sign up to set email alerts
|

Sur la symétrie dans les phénomènes physiques, symétrie d'un champ électrique et d'un champ magnétique

Abstract: To cite this version: P. Curie. Sur la symétrie dans les phénomènes physiques, symétrie d'un champélectrique et d'un champ magnétique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
413
2
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(430 citation statements)
references
References 0 publications
8
413
2
7
Order By: Relevance
“…It is interesting to interpret our results in the context of Curie's principle [25], which asserts that the symmetries of the causes must be found in the effects. Asymmetryinduced symmetry requires that 1) any state with the symmetry of the system be unstable and hence not observed and 2) the symmetry of the system be reduced to realize the symmetric state-both consistent with but not following from Curie's principle.…”
mentioning
confidence: 89%
“…It is interesting to interpret our results in the context of Curie's principle [25], which asserts that the symmetries of the causes must be found in the effects. Asymmetryinduced symmetry requires that 1) any state with the symmetry of the system be unstable and hence not observed and 2) the symmetry of the system be reduced to realize the symmetric state-both consistent with but not following from Curie's principle.…”
mentioning
confidence: 89%
“…Then I has a Gamma-mixture distribution, which is described by a cumulant-generating function By virtue of Eqs. (12)(13), each term of the summation r j in Eq. (B2) is an independent Gamma-distributed random variable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the necessity of broken symmetry was already pointed out by P. Curie in 1894 [28], it took until the 1960s that Soviet scientists found the first material exhibiting static magnetoelectric coupling [29,30]. Dzyaloshinskii found that piezoelectric Cr 2 O 3 displays long-range magnetic order and thus breaks time reversal symmetry [31].…”
Section: Development Of Mec In Insulatorsmentioning
confidence: 99%